Multivariate analysis of histopathological features as prognostic factors in fifty cases of thyroid neoplasm: a retrospective study done at tertiary care centre - Bhandari, Hitesha; Sharma, Anjali; Nilapwar, Rishikesh D.; Vyas, Praveena G.; Pawar, Aditya S. (International Journal of Research in Medical Sciences, 2024)
Background: Number of prognostic factors for thyroid carcinoma have been identified including age, gender and tumor characteristics, such as histology and stage. The importance of these factors as independent predictors of survival for patients with differentiated thyroid carcinoma has been extensively studied but remains uncertain. Methods: A retrospective analysis of 50 thyroid carcinomas was made to assess prognostic factors including histological variants from September 2019 to February 2022 at our centre. The surgical and histopathological data were studied. Results: 72% patients had papillary thyroid cancer. Multivariate analysis was done and factors showing prognostic significance were tumour size, extrathyroid extension, extranodal extension, lymphovascular, perineural invasion, histological type, necrosis, focality, capsular invasion were found to have poor prognosis. Conclusions: There are histopathological factors which can modify the course and influence the line of treatment of thyroid neoplasms.